Mutations as Levy flights - Dario A. Leon (Nature Portfolio, 2021)
Abstract Data from a long time evolution experiment with Escherichia Coli and from a large study on copy number variations in subjects with European ancestry are analyzed in order to argue that mutations can be described as Levy flights in the mutation space. These Levy flights have at least two components: random single-base substitutions and large DNA rearrangements. From the data, we get estimations for the time rates of both events and the size distribution function of large rearrangements.